1993
DOI: 10.1111/j.1751-9861.1993.tb00031.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Stress on Natural Killer Cell Activity in Healthy Men1

Abstract: Several studies have shown that exposure to acute laboratory stressors produces an immediate change in immune function. We examined the effects of a mild laboratory stressor on natural killer (NK) cell cytotoxicity and on psychological and cardiovascular measures in 24 adult males. Subjects in the experimental condition worked on the Stroop task without interference for 30 min with blood samples drawn at baseline, 10, 20, and 30 rnin into the task, and 40 rnin after completing the task. The 30-min stressor pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…Consistent with previous studies (L. Cohen et al, 1993;Manuck et al, 1991;Zakowski et al, 1992), we found some relationships between cardiovascular measures during the task and immune responses. This relationship was positive for NK cell activity, with greater increases in HR and DBF in the first 2 min of the stressor predicting greater increases in NK cell activity during the stressor.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with previous studies (L. Cohen et al, 1993;Manuck et al, 1991;Zakowski et al, 1992), we found some relationships between cardiovascular measures during the task and immune responses. This relationship was positive for NK cell activity, with greater increases in HR and DBF in the first 2 min of the stressor predicting greater increases in NK cell activity during the stressor.…”
Section: Discussionsupporting
confidence: 92%
“…The decrease in activity below baseline at the end of the present experiment was not significant, possibly because we did not continue measurement long enough. Studies reporting a decrease in NK cell activity have observed this decrease at more distal time points than the ones we measured (L. Cohen et al, 1993;Sieber et al, 1992). Had we measured NK cell activity at 30-60 min after stressor termination, we might have observed decreased activity.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Number of NK cells (CD56+ cells) did not change throughout the experiment. Decreased NK activity (cell numbers were not measured) has also been noted 40 min after the end of a 30-min Stroop task (Cohen et al, 1993). However, a number of studies have found increases in number and activity of NK cells during and following exposure to a Douglas L. Delahanty, Department of Psychology, Kent State University; Taiping Wang, Craig Maravich, Michael Forlenza, and Andrew Baum, Department of Psychology, University of Pittsburgh.…”
mentioning
confidence: 99%